Organized crime and American power: a history - Woodiwiss, Michael (University of Toronto Press, 2024)
"Popular histories of organized crime in the United States often look to the "Mafia" and the sons of early twentieth-century immigrants--such as Al Capone, Lucky Luciano, and Meyer Lansky--for their origins. In this second edition of Organized Crime and American Power, Michael Woodiwiss refocuses on US organized crime as an American problem. The book starts in 1789, with the birth of a new nation, intended to be run according to laws and conventions, with a written commitment to civil rights. Woodiwiss examines the organization of crime before the Civil War, which damaged or destroyed the lives of those excluded from constitutional protections: Native Americans, African Americans, and women. The book focuses on white supremacist crime and the pernicious influence of Southern leaders in alliance with opportunistic politicians. It examines the organized crimes of powerful business interests in alliance with politicians, as well as the corrupt consequences of the US moralistic campaigns against alcohol, gambling, drugs, and abortion. Organized Crime and American Power brings solid historical evidence and analysis to the task of refuting conventional wisdom that frames organized crime as something external to US political, economic, and social systems."--